Transarterial occlusion of solitary intracerebral arteriovenous fistulas. - Halbach, V V; Higashida, R T; Hieshima, G B; Hardin, C W; Dowd, C F; Barnwell, S L (American Journal of Neuroradiology, 1989)
Congenital solitary arteriovenous fistulas unassociated with arteriovenous malformations are rare. Five patients with this condition were treated by endovascular procedures: three by transarterial balloon occlusion and two by coil and silk suture embolization. Of the three patients treated by balloon occlusion, complete angiographic obliteration was achieved in two, and one patient had subtotal occlusion resulting from proximal balloon placement. Two of these patients subsequently underwent surgical excision without incident. There were no complications. Two patients were treated with a combination of platinum coils and silk suture embolization, which resulted in complete angiographic obliteration in both. There was one asymptomatic complication consisting of a coil migrating through the fistula and lodging in the lung. While detachable balloons have advantages in allowing test occlusion prior to detachment, the traction required for detachment can limit accurate deposition and place the feeding arteries under undue stretch. Coil and silk suture embolization enable more precise deposition and are probably the agent of choice for closure of solitary arteriovenous connections within the central nervous system.